Pengaruh Persepsi Harga, Kualitas Produk dan Kualitas Pelayanan Terhadap Keputusan Pembelian Ini Baru Steak Boyolali - Vika Ayu Saputri; Acharina Pratiwi (Universitas 45 Surabaya, 2024)
The aim of this research is to analyze the influence of price perceptions, product quality and service quality on consumer purchasing decisions. The population in this study were Ini Baru Steak Boyolali consumers with a sample size of 100 determined using a purposive sampling technique.The results of the analysis stated that all questionnaire items as research instruments were valid and reliable, as well as the classical assumption tests, including the multicollinearity test, autocorrelation test, heteroscedasticity test and normality test, all variables were declared to have passed the classical assumption test. Meaning that all regression coefficients are positive, which means that variables X1 (price perception), X2 (product quality) and X3 (service quality) have an effect positive towards purchasing decisions on Ini Baru Steak Boyolali. Hypothesis testing shows that price perception has a significant effect on purchasing decisions at Ini Baru Steak Boyolali. Product quality has a significant influence on purchasing decisions at Ini Baru Steak Boyolali. Service quality has a significant influence on purchasing decisions at Ini Baru Steak Boyolali. The F test states that the research model for the influence of the independent variable on the dependent variable is correct. The coefficient of determination test shows that perceptions of price, product quality and service quality can explain purchasing decisions by 69.1%.